Microbiological Diversity and Associated Enzymatic Activities in Honey and Pollen from Stingless Bees from Northern Argentina - Salomon, Virginia María; Hero, Johan Sebastian; Morales, Andrés Hernán; Pisa, José Horacio; Maldonado, Luis Maria; Vera, Nancy Roxana; Madrid, Rossana Elena; Romero, Cintia Mariana (MDPI, 2024)
Honey and pollen from Tetragonisca fiebrigi and Scaptotrigona jujuyensis, stingless bees from northern Argentina, presented a particular microbiological profile and associated enzymatic activities. The cultured bacteria were mostly Bacillus spp. (44%) and Escherichia spp. (31%). The phylogenetic analysis showed a taxonomic distribution according to the type of bee that was similar in both species. Microbial enzymatic activities were studied using hierarchical clustering. Bacillus spp. was the main bacterium responsible for enzyme production. Isolates with xylanolytic activity mostly presented cellulolytic activity and, in fewer cases, lipolytic activity. Amylolytic activity was associated with proteolytic activity. None of the isolated strains produced multiple hydrolytic enzymes in substantial amounts, and bacteria were classified according to their primary hydrolytic activity. These findings add to the limited knowledge of microbiological diversity in honey and pollen from stingless bees and also provide a physiological perspective of this community to assess its biotechnological potential in the food industry.